Improving farmers' livelihoods through conservation agriculture: options for change promotion in Laikipia, Kenya. Issue 3 (3rd May 2020) - Ndah, Hycenth Tim; Probst, Lorenz; Kaweesa, Sara; Kuria, Peter; Mkomwa, Saidi; Rodrigues, Paulo; Basch, Gottlieb; Uckert, Götz; Sieber, Stefan; Knierim, Andrea; Zander, Peter; Schuler, Johannes
ABSTRACT: Across Sub-Saharan Africa, agricultural practices for sustainable intensification need to be up-scaled from project interventions to institutional mainstreaming. However, several constraints, including a general lack of resources and knowledge, limited institutional support and challenging market conditions hamper this process. The objective of this study was to develop region-specific options to promote Conservation Agriculture (CA) in the Laikipia region, Kenya. We applied the Transformative Learning Approach (TLA) to stimulate and nurture a joint learning process around CA, to diagnose hindering and supporting factors for up-scaling of CA and to develop options for change promotion. Through a series of field visits, we collected and analyzed data using elements of the TLA approach: i.e. agro-ecosystem health check, stakeholder mapping, participatory videos and the Qualitative Assessment tool for CA adoption (QAToCA). Our findings reveal that up-scaling of CA is hindered by inefficient agricultural market structures, limited access to CA specific biological (residue, seeds), and technical inputs (e.g. machinery), a lack of finances, and absence of knowledge. We recommend four options for further CA promotion in the region: localised expertise (e.g. crop-livestock integration), unbiased facilitation (e.g. careful choice of multipliers), subsidized inputs (e.g. micro-credits) and robust institutional system support (e.g. stable agricultural policies).